The characteristics of healthy adults with hardly palpable vein—Relations between easy venous palpation and physical factors. Issue 6 (14th April 2014) - Ichimura, Mika; Matsumura, Yuko; Sasaki, Shinsuke; Murakami, Naoki; Mori, Masaharu; Ogino, Tetsuya
Abstract : This study aimed to investigate relations between ease of venous palpation and various venous factors, and to elucidate characteristics of hardly palpable veins. Healthy adult volunteers ( n = 110) were enrolled. The ease of venous palpation was scored from 0: impalpable to 3: well palpable. Venous factors, namely venous depth, elevation, area and minimal pressure that starts to collapse vein, were measured using an ultrasonography before and after tourniquet inflation at 60 mmHg for 60 s. Tourniquet inflation significantly increased the venous area and venous palpation score. The four venous factors correlated significantly with venous palpation score with the following correlation coefficient: Depth ( r = −0.542), Elevation (0.486), area (0.258) and start‐to‐collapse pressure (−0.220). The characteristics of hardly palpable veins were small size, deep location and little elevation. Although vasodilatation facilitated venous palpation, venous depth and elevation were also important and should be included in future studies in which vasodilatation methods are evaluated.